2022
DOI: 10.1021/acsnano.2c10404
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasoft and Biocompatible Magnetic-Hydrogel-Based Strain Sensors for Wireless Passive Biomechanical Monitoring

Abstract: Implantable flexible mechanical sensors have exhibited great potential in health monitoring and disease diagnosis due to continuous and real-time monitoring capability. However, the wires and power supply required in current devices cause inconvenience and potential risks. Magnetic-based devices have demonstrated advantages in wireless and passive sensing, but the mismatched mechanical properties, poor biocompatibility, and insufficient sensitivity have limited their applications in biomechanical monitoring. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Screening of mycelial forms of filamentous fungi using FADS requires a long and stable culture for accurate analysis. Gel-MA is a highly biocompatible material that has been used in cell culture and tissue engineering. , This study demonstrated that core–shell droplets of Gel-MA material can support the entire growth process of A. niger for up to 2 days, including spore germination and mycelial extension, which is a more accurate representation of the actual fermentation process of A.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Screening of mycelial forms of filamentous fungi using FADS requires a long and stable culture for accurate analysis. Gel-MA is a highly biocompatible material that has been used in cell culture and tissue engineering. , This study demonstrated that core–shell droplets of Gel-MA material can support the entire growth process of A. niger for up to 2 days, including spore germination and mycelial extension, which is a more accurate representation of the actual fermentation process of A.…”
Section: Discussionsupporting
confidence: 93%
“…Gel-MA is a highly biocompatible material that has been used in cell culture and tissue engineering. 25,34 This study demonstrated that core−shell droplets of Gel-MA material can support the entire growth process of A. niger for up to 2 days, including spore germination and mycelial extension, which is a more accurate representation of the actual fermentation process of A. niger. The present results suggest that spores grow faster inside the droplet than inside the flask, which is consistent with a previous report.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Examples of transducers encompass temperature [ 82 , 83 ], pressure/strain [ 84 , 85 ], and ion concentration transducers, among others. Recently, Qi Zhang et al introduced a magnetic-hydrogel-based soft strain transducer that exploits the relative magnetic field changes of a gelatin methacrylate (GelMA)/Fe 3 O 4 magnetic hydrogel film, as illustrated in Figure 5 a [ 86 ]. This material exhibits excellent magnetic properties (12.74 emu/g), great biocompatibility, desired stability, and a very low Young’s modulus that renders it ultrasoft.…”
Section: Nanomaterial-enabled Wearable Electronicsmentioning
confidence: 99%
“… ( a ) A strain transducer based on (GelMA)/Fe 3 O 4 –magnetic hydrogel film (reprinted with permission from Ref. [ 86 ], Copyright 2022 American Chemical Society). ( b ) A pressure transducer array made of graphene nanoparticles (reprinted with permission from Ref.…”
Section: Figurementioning
confidence: 99%
“…As a material that directly contacts human skin, the biocompatibility is a key issue to be considered in designing wearable strain sensors. 117 For instance, Xu et al 118 have fabricated a capacitive strain sensor composed of ionic hydrogel and silver nanofibers (AgNFs). The sensor showed no skin irritation even after the volunteer wore the sensor for 4 days, exhibiting excellent biocompatibility (Figure 11A).…”
Section: Biocompatibilitymentioning
confidence: 99%